Study of risk factor resulting in occurrence of lumbar syndrome in nurses - Peković Dragana (Association of Nurses Technicians and Midwives, 2018)
Lower back pain which occurs in people who work every day is the most usual reason to visit a doctor, and it is the first reason to become unable to work. Professions bearing a high risk of occurrence of lumbar syndrome fall within the field of healthcare. Objective: Studying the frequency of some risk factors resulting in occurrence of lumbar syndrome in nurses employed in tertiary health care. Method: The research included 87 subjects employed within the field of tertiary healthcare. Modified Nordic questionnaire was used as the instrument for risk factor assessment and for collection of data. Results: Results obtained from this research were analysed in compliance with the defined objective. Out of the total number of subjects, 87% of subjects stated that they experienced a lower back pain during the previous year. The pain was characterised as moderate by 55% of subjects and as such it is predominantly present in female subjects, in the group of subjects aged from 41 to 50, who have been employed from 11 to 20 years. Severe and strong pain was dominant of subjects who have been employed for more than 30 years. 92% of subjects who work in shifts have experienced lumbar pain. Lifting weight heavier than 25 kg is specified as the most frequent factor. Conclusion: Results obtained from this research correspond to the results obtained from researches performed globally and locally. In order to reduce the frequency of lumbar pain occurrence in nurses-technicians, it is necessary to implement preventive measures. Preventive measures are to be implemented by individuals, organization and wider social network.